IMANOLEN ARROBIA: A NEW UPPER PLEISTOCENE CARNIVORE DEN IN THE NORTH OF THE IBERIAN PENINSULA (DEBA, SPAIN) (Ameghiniana, 2017)
A taphonomic and systematic study of an assemblage of large mammals preserved in an early Upper Pleistocene deposit in Imanolen Arrobia (Deba, northern Spain) is hereby reported. Skeletal profiles, long bone fragmentation and tooth marks reveal that carnivores transported wild goats and chamois carcasses to the cave for their consumption. The abundance of juvenile remains suggests that these carnivores preferentially preyed on immature individuals. After considering the frequencies of different carnivores in the assemblage and other taphonomic and neo-taphonomic features and, even though the wolf (Canis lupus) cannot be completely discarded, the leopard (Panthera pardus) is proposed as the plausible responsible for the hunting and transport of the ungulate remains to the cave. The bones were subsequently probably modified by foxes (Vulpes vulpes) that used the cave as a breeding den. By way of comparative data from the Cantabrian region and especially from the Basque Country, a metric study drawing comparisons between the most frequent species (Capra pyrenaica, Rupicapra pyrenaica, Panthera pardus and Vulpes vulpes) evinces that the Imanolen Arrobia measurements are within the range of variation of fossil species in the northern Iberian Peninsula. Resumen. IMANOLEN ARROBIA: NUEVO CUBIL DE CARNÍVOROS EN EL NORTE DE LA PENÍNSULA IBÉRICA (DEBA, ESPAÑA) DURANTE EL INICIO DEL PLEISTOCENO SUPERIOR. En este trabajo se ofrece el estudio tafonómico y sistemático de un conjunto de macromamíferos recuperados del depósito de Imanolen Arrobia (Deba, norte de España) correspondiente al inicio del Pleistoceno Tardío. Los perfiles esqueléticos, la fragmentación de los huesos largos y las marcas de dientes en los huesos, son prueba de que la cabra montés y el rebeco fueron transportados a la cueva y consumidos por carnívoros. La abundancia de restos de individuos juveniles indica que los carnívoros cazaron preferentemente animales inmaduros. Tras considerar las frecuencias de restos de distintos carnívoros presentes en la muestra así como otros datos tafonómicos y neotafonómicos, se propone al leopardo (Panthera pardus) como posible responsable de la caza y transporte de los restos de ungulados a la cueva aunque sin descartar tampoco al lobo (Canis lupus). El conjunto óseo fue posteriormente modificado probablemente por zorros (Vulpes vulpes) que utilizaron la cueva como cubil de cría. Se ofrece un estudio métrico comparativo de las especies más frecuentes (Capra pyrenaica, Rupicapra pyrenaica, Panthera pardus y Vulpes vulpes) utilizando datos de la región Cantábrica y en especial del País Vasco. Se constata que las medidas de los ejemplares de Imanolen Arrobia entran dentro del dominio de variación de sus congéneres fósiles del norte de la Península Ibérica.